Skewness in Stock Returns: Reconciling the Evidence on Firm Versus Aggregate Returns - Albuquerque, Rui (Review of Financial Studies, 2012)
Aggregate stock market returns display negative skewness. Firm stock returns display positive skewness. The large literature that tries to explain the first stylized fact ignores the second. This article provides a unified theory that reconciles the two facts by explicitly modeling firm-level heterogeneity. I build a stationary asset pricing model of firm announcement events where firm returns display positive skewness. I then show that cross-sectional heterogeneity in firm announcement events can lead to conditional asymmetric stock return correlations and negative skewness in aggregate returns. I provide evidence consistent with the model predictions. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.